Morphological Comparisons of Adult Worker Bees Developed in Chinese and Italian Honey Bee Combs - Shunhua Yang; Hui Li; Pingqing Wu; Dan Yue; Yulong Guo; Wenzheng Zhao; Kun Dong (Insects)
The size of comb cells is a key factor influencing the body size of honey bee workers. Comb cells and the body size of Chinese honey bee workers are smaller than those of Italian honey bee workers. To increase the size of Chinese honey bee workers, this study used newly built combs from Chinese honey bee colonies (control group) and Italian honey bee colonies (treatment group). These combs were provided to Chinese honey bee colonies for queens to lay fertilized eggs with the aim of rearing larger workers. Workers emerging from the control and treatment combs were designated as control and treatment workers, respectively. We compared 13 external morphological traits, including right forewing length and width; linear length of veins a, b, c, and d; proboscis length; right hind femur length; tibia length; metatarsal length and width; and the longitudinal diameters of the third and fourth tergites between the two groups. The results identified six types of cell contents in the combs, excluding empty cells: capped honey (most abundant), followed by capped brood, uncapped honey, and smaller amounts of pollen, larvae, and eggs. Additionally, the average body weights of 6-day-old worker bee larvae, white-eyed pupae, adult worker bees, and honey stomachs containing sucrose solution were significantly higher in the treatment group than in the control group. Except for proboscis length, the average size of 12 out of 13 traits in the treatment group was significantly larger than in the control group, indicating that increasing cell size can produce larger Chinese honey bee workers. In the control group, only the left forewing was significantly shorter than the right, with no significant side-to-side differences in the other morphological traits. In the treatment group, the left forewing width, hind leg femur length, tibia length, and hind leg metatarsus width were significantly smaller than their right-side counterparts, while the other six traits showed no significant side-to-side differences. These findings provide a basis for using Italian honey bee combs to rear larger workers in Chinese honey bee colonies, offering beekeepers a strategy to enhance foraging capacity and improve honey production.